Acute effects of neuromuscular electrical stimulation on vertical jump performance - Kaire, Y.; Harveson, A.; Garrett, L.; Sturz, D. (International Journal of Sports Science, 2020)
Understanding the acute effects neuromuscular electrical stimulation (NMES) applied to the quadriceps group can have on vertical jump was the primary objective of this study. Multiple studies have indicated improvements in muscular strength, power, and performance can be made over time through NMES. This study is unique because no previous studies have conducted research into the effects of NMES on vertical jump immediately after isometric stimulation to the quadriceps group. A group of 24 subjects were randomly divided into equal 12-member experimental and control groups. All subjects were pretested in the countermovement jump (CMJ) to determine maximum jumping height. Treatment consisted of placing electrodes on the quadriceps of members of the experimental group and turning the Marc Pro Device on 1.7 Hz for 15-minutes. Sham treatment consisted of placing electrodes on the quadriceps of members of the control group and turning the Marc Pro Device on 0.0 Hz for 15-minutes. All subjects then engaged in a post treatment CMJ test. The difference between pretest and posttest jump scores was computed to determine the effects of treatment. A statistically significant increase in experimental group CMJ scores occurred from pre-test to posttest (p < .05). It was hypothesized that an increase in blood flow and activation of the fast-twitch muscle fiber to the applied muscle group facilitated increased muscular power. NMES is an easily applied performance enhancement strategy that could be an important addition to athletes and active individuals.